(untitled) (Proceedings of the Institute of Biology, 2023)
The Numrug Strictly Protected Area (SPA) in eastern Mongolia serves as a unique ecological region, encompassing diverse landscapes from medium-low mountains to forests, meadows, and steppes. It was established in 1992, with subsequent expansion in 2019 to preserve the Khingan ecosystem and Manchuria’s rich biodiversity. A total of 57 mammal species belonging to seven orders were identified in Numrug SPA, representing 39.3% of Mongolia’s recorded mammal species after its expansion of 1.8 more in territory size and increases in habitats. Notably, 15 of these species hold regional and international endangered statuses, emphasizing the ecological significance of the area. The analysis reveals that river valleys and mountain steppes as key habitats to mammal diversity and warrants possible new species or registration in the species richness of Chiroptera and Rodentia in further.